Development of Thematic Research Framework to Support Activator Teacher Program in Elementary School (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to provide meaningful, in-depth and student-centered learning at elementary level. Through the development of thematic research framework as to respond to Activator Teacher Program launched by the Ministry of Education and Culture, teachers can provide quality learning. Activator Teachers as learning leaders have more roles and capacities than just teachers in the classroom. Activator Teacher is directed to have a growth mindset that is willing to learn and equip themselves, open and response positively to new things. Thematic research framework offers more of students’ engagement in the learning process and develops students’ research skills through each step of the research. This study is conducted through Research and Development method, ADDIE model. The results show that thematic research framework is effective. The effectiveness criteria are analyzed based on the results of the questionnaires returned by 19 students of grade 6 with an average of 4.2, the result of interview with subject teacher that indicates a meaningful, in-depth and student-centered learning through the process and the percentage of learning outcomes from 10 randomly selected students that reach 80% of accomplishment.